In reply: Anesthesia and multiorgan protein remodeling: correspondence - Fütterer, Carsten Dietmar; Maurer, Martin H.; Kuschinsky, Wolfgang; Waschke, Klaus F. (Anesthesiology, 2004)
An abstract is unavailable.
Gesehen am 14.01.2025